Risk of Recommendations : Human Rights Perspective on the Recommender Systems of Social Media Platforms - Valtimo, Heini (My University, 2023)
This thesis examines the recommender systems of social media platforms and whether those are risking human rights. The issue is analysed from the perspective of the right not to be manipulated, which is considered to be an element part of both freedom of opinion and freedom of thought. The first part provides a deeper look into the scope of freedom of opinion and freedom of thought as protected in the International Covenant on Civil and Political Rights and the European Convention on Human Rights, supported by the Charter of the Fundamental Rights of the European Union. The background analysis of freedom of thought and freedom of opinion shows that although the international human rights law system slightly differs from the European framework, both frameworks offer protection against manipulation. The second part of this thesis focuses on the Digital Services Act and its rules concerning recommender systems of very large online platforms. The aim is to analyse whether those rules are enough to protect the rights of the users from the perspective of the right not to be manipulated. It is concluded that while the Digital Services Act protects the right not to be manipulated, e.g., by improving the transparency requirements of the platforms, it could have been more ambitious. The third part tries to analyse the issue from an international perspective and provide alternative solutions. The thesis follows a hermeneutical methodology, with an attempt to approach the topic with an orientation that seeks to achieve a deeper understanding of the phenomenon by trying to enhance the interpretive experience. Legal dogmatics is used when the human rights in question are presented as they appear in human rights treaties. Furthermore, the same approach is used to analyse the rules of the DSA. Moreover, the analysis includes comparative methods as well as elements of socio-legal analysis. Since neither the freedom of opinion nor freedom of thought does not have much jurisprudence explaining their importance in the digital context, an attempt is made to examine the scope and the significance of those rights in the information society we live in today.
Keywords: Right not to be manipulated, Freedom of opinion, Freedom of thought, Digital Services Act